Trends in mortality among ART-treated HIV-infected adults in the Asia-Pacific region between 1999 and 2017: results from the TREAT Asia HIV Observational Database (TAHOD) and Australian HIV Observational Database (AHOD) of IeDEA Asia-Pacific - Jung, In Young; Rupasinghe, Dhanushi; Woolley, Ian; O'Connor, Catherine C.; Giles, Michelle; Raja Azwa, Raja Iskandar; Choi, Jun Yong (Wiley Open Access, 2019)
Introduction: AIDS-related deaths in people living with HIV/AIDS have been decreasing in number since the introduction of combination antiretroviral treatment (cART). However, data on recent causes of death in the Asia-Pacific region are limited. Hence, we analysed and compared AIDS-related and non-AIDS–related mortality in high- and low-income settings in the region. Methods: Patients from the TREAT Asia HIV Observational Database (TAHOD) and Australian HIV Observational Database (AHOD) receiving cART between 1999 and 2017 were included. Causes of death verification were based on review of the standardized Cause of Death (CoDe) form designed by the D:A:D group. Cohorts were grouped as AHOD (all high-income sites), TAHOD-high (high/upper-middle income countries) and TAHOD-low (lower-middle income countries). TAHOD sites were split into high/upper-middle income and lower-middle income country settings based on World Bank classifications. Competing risk regression was used to analyse factors associated with AIDS and non-AIDS–related mortality. Results: Of 10,386 patients, 522 died; 187 from AIDS-related and 335 from non-AIDS–related causes. The overall incidence rate of deaths during follow-up was 0.28 per 100 person-years (/100 PYS) for AIDS and 0.51/100 PYS for non-AIDS. Analysis indicated that the incidence rate of non-AIDS mortality decreased from 0.78/100 PYS to 0.37/100 PYS from year groups 2003 to 2007 to 2013 to 2017 (p < 0.001). Similarly, incidence rates of AIDS-related deaths decreased from 0.51/100 PYS to 0.09/100 PYS from year groups 2003 to 2007 to 2013 to 2017 (p < 0.001). More recent years of follow-up were associated with reduced hazard for non-AIDS mortality (2008 to 2012: aSHR (adjusted sub-hazard ratio) 0.72, 95% confidence interval (CI) 0.54 to 0.96, p = 0.027; 2013 to 2017: aSHR 0.64, 95% CI 0.47 to 0.87, p = 0.004) compared to years 2003 to 2007. The AHOD cohort had almost twice the hazard of non-AIDS mortality compared to TAHOD-low (lower-middle income sites) (aSHR 1.72, 95% CI, 1.20 to 2.46, p = 0.003); there were no differences between cohorts for AIDS-related mortality (p = 0.834). Conclusion: AIDS and non-AIDS–related mortality rates have decreased over the past years in the Asia-Pacific region. There is a greater risk for non-AIDS–associated deaths in the AHOD cohort compared to lower-middle income settings in TAHOD. © 2019 The Authors. Journal of the International AIDS Society published by John Wiley & Sons Ltd on behalf of the International AIDS Society.